A Review on Ã¢â‚¬Å“Ethosomes: An Emerging Approach for Drug Delivery through the SkinÃ¢â‚¬Â - Shailesh S1, Chauhan P1, Upadhyay N1*, Mandal S2, Bhatia L3, (Recent Research in Science and Technology, 2011)
Ethosomes are the ethanolic phospholipid vesicles which are used mainly for transdermal delivery of drugs. Ethosomes have higher penetration rate through the skin as compared to liposomes hence these can be used widely in place of liposomes. The increased permeation of ethosomes is probably due to its ethanolic content. Ethanol increases the cell membrane lipid fluidity which results in increased skin penetrability of the ethosomes. Transdermal administration of drugs is generally limited by the barrier function of the skin. Vesicular systems are one of the most controversial methods for transdermal delivery of active substances. The interest in designing transdermal delivery systems was relaunched after the discovery of elastic vesicles: transferosomes and liposomes. This article reviews various aspect of ethosomes including their preparation, characterization, potential advantages and their applications in drug delivery. Because of their unique structure, ethosomes are able to encapsulate and deliver through the skin highly lipophilic molecules such as cannabinoids, testosterone, andminoxidil, as well as cationic drugs such as propranolol, trihexyphenidil, Cyclosporine A, insulin, salbutamol etc.. Ethosomes provides a number of important benefits including improving the drug’s efficacy, enhancing patient compliance and comfort and reducing the total cost of treatment.